Focal chorioretinitis in thailand - Kessara Pathanapitoon (2018)
PURPOSE:: To report the clinical features of patients with focal chorioretinitis (FCR), as well as toxoplasma serology. METHODS:: We included 25 (4%) consecutive patients with FCR of 593 with uveitis. Controls consisted of 127 patients with posterior and panuveitis and clinical features other than FCR. Results of enzyme-linked immunosorbent assay for anti-Toxoplasma gondii immunoglobulin G (IgG) and IgM, demographic data, and clinical features of patients were registered. RESULTS:: Positive anti-T. gondii IgG levels were observed in 21 of 25 patients (84%) with FCR in contrast to 14 of 127 patients (11%) with non-FCR (P < 0.001, Fisher test). The IgG levels >600 IU were found in 19 of 25 patients (76%) with FCR and in none of the patients with non-FCR (P < 0.001). All cases had unilateral involvement. Ocular features consisting of FCR and vitritis were present in all patients, but associated chorioretinal atrophic scars were not commonly seen (7/25 eyes; 28%). Retinal vasculitis was found in 9 of 25 eyes (36%) and affected solely the arteries. CONCLUSION:: The majority of patients with FCR in Thailand exhibit highly positive anti-T. gondii IgG levels suggesting the presence of active systemic infection, which is also consistent with the absence of old scars. The absence of old scars and retinal arteritis were the features distinct from typical ocular toxoplasmosis lesions reported in the European and the U.S. series. © 2013 Ophthalmic Communications Society, Inc.